TINJAUAN HUKUM ISLAM TENTANG PRAKTIK JASA WALI NIKAH SIRRI DI BEKASI - Mustakim, Muhammad Arfian; Suprihatin, Suprihatin; Supriyanto, Agus (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2023)
Marriage is a sacred ritual that religious and state laws must legalize. Most people want marriage to be a joyous occasion and a way to publicize their status as husband and wife. However, some people keep their marriages secret. In general, Nikah Sirri celebrates a marriage according to Islamic religious rules. However, many things prevent it from being legally recorded by the authorities, in this case, the government, represented by the Ministry of Religious Affairs. This research aims to investigate providers of marriage guardian services in siri marriages that have developed in the community through social media. One of these providers can be found on the website ustadz.my.id/jasa-nikah-siri-bekasi, which offers various services related to siri marriages. This research uses qualitative methods and is centered on empirical research. This research uses a socio-legal approach, a broad social science methodological approach. as the Wali Nikah in Sirri Nikah Services. This study conducted the data collection method in two stages: observation and documentation. The study found that because there is an element of gharar or uncertainty, the practice of providing a marriage guardian in a sirri marriage through a website whose address is ustadz.my.id/jasa-nikah-siri-bekasi is not justified by Islamic legal review. Thus, this element of gharar hinders the practice of providing marriage guardians in sirri marriages. This is in line with the prohibition of the prophet Muhammad to avoid buying and selling gharar.